Jethro Tull's Thick as a Brick and A Passion Play : Inside Two Long Songs - Smolko, Tim (Book collections on Project MUSE., 2013)
Since the 1960s, British progressive rock band Jethro Tull has pushed the technical and compositional boundaries of rock music by infusing its musical output with traditions drawn from classical, folk, jazz, and world music. The release of Thick as a Brick (1972) and A Passion Play (1973) won the group legions of new followers and topped the Billboard charts in the United States, among the most unusual albums ever to do so. The author explores the large-scale form, expansive instrumentation, and complex arrangements that characterize these two albums, each composed of one continuous song.